Analisis Retorika Anies Baswedan Dalam Mengangkat ISU Pendidikan Di Indonesia Pada Debat Calon Presiden Pemilu Tahun 2024 - Dama, Yunus; Tuzzahra Bachri, Sitti Fatimah; Murad, Putri Salsabilah; Zain, Miranda; Minasi, Sastia; Rajak, Juriyati; Datau, Cindra (Jurusan Pendidikan Bahasa & Sastra Indonesia, Universitas Negeri Gorontalo, 2025)
This study aims to analyze Anies Baswedan's rhetorical style in addressing educational issues during the 2024 presidential candidate debates and to compare it with other candidates. The research employs a descriptive qualitative method with an Aristotelian rhetorical approach, focusing on the elements of ethos, pathos, and logos in Anies Baswedan's speeches. Data is collected through literature review, examining relevant journals, books, articles, other written sources related to the research topic. The findings indicate that Anies Baswedan utilizes a formal rhetorical style, emphasizing clear vision and mission statements, and builds credibility through his experience and knowledge in the field of education. However, his formal and academic communication style is sometimes perceived as less relatable by some audiences. In comparison, other candidates like Prabowo Subianto and Ganjar Pranowo exhibit distinct rhetorical styles. Prabowo is known for his relaxed and approachable speaking style, using simple and easily understandable language for the general public. Meanwhile, Ganjar Pranowo adopts a more populist approach, incorporating humor and anecdotes in his speeches. The combination of strengths and weaknesses in Anies Baswedan's rhetoric influences public perception of his commitment to education. His credibility and experience instill confidence in his potential to bring positive change. However, the lack of detailed explanations regarding program implementation may raise doubts about the effectiveness of the proposed plans. It is crucial for Anies to balance the delivery of vision and mission with concrete action plans to convince the public of his seriousness in improving the education sector, Anies Baswedan's rhetorical style in addressing educational issues has strengths in terms of credibility.